2016
DOI: 10.1364/oe.24.030173
|View full text |Cite
|
Sign up to set email alerts
|

Non-degenerate 2-photon excitation in scattering medium for fluorescence microscopy

Abstract: Non-degenerate 2-photon excitation (ND-2PE) of a fluorophore with two laser beams of different photon energies offers an independent degree of freedom in tuning of the photon flux for each beam. This feature takes advantage of the infrared wavelengths used in degenerate 3-photon excitation (D-3PE) microscopy to achieve increased penetration depths, while preserving a relatively high 2-photon excitation cross section in comparison to that of D-3PE. Here, using spatially and temporally aligned Ti:Sapphire laser … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 51 publications
(78 reference statements)
0
12
0
Order By: Relevance
“…41 For confocal fluorescence imaging, and taking into account the Stokes shift, Figure 5b,c shows that the l con reached the maximum values with three pairs of excitation and emission wavelengths: (1) excitation in the 1300 nm window and emission in the 1700 nm window (this work), (2) excitation in the 1700 nm window and emission in the 2200 nm window, Therefore, in addition to the results shown here, there are additional opportunities for long-wavelength confocal fluorescence imaging if appropriate fluorescent labels exist. We note that the considerations for the wavelength selections discussed here are also applicable to nonlinear excitations where two or more wavelengths are employed for excitation such as nondegenerate two-photon excitation, 48 stimulated Raman scattering, 49 and pump−probe imaging. 50,51 With the estimated confocal signal attenuation length, we can determine the absolute imaging depth limit of fluorescence confocal microscopy in the following section.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…41 For confocal fluorescence imaging, and taking into account the Stokes shift, Figure 5b,c shows that the l con reached the maximum values with three pairs of excitation and emission wavelengths: (1) excitation in the 1300 nm window and emission in the 1700 nm window (this work), (2) excitation in the 1700 nm window and emission in the 2200 nm window, Therefore, in addition to the results shown here, there are additional opportunities for long-wavelength confocal fluorescence imaging if appropriate fluorescent labels exist. We note that the considerations for the wavelength selections discussed here are also applicable to nonlinear excitations where two or more wavelengths are employed for excitation such as nondegenerate two-photon excitation, 48 stimulated Raman scattering, 49 and pump−probe imaging. 50,51 With the estimated confocal signal attenuation length, we can determine the absolute imaging depth limit of fluorescence confocal microscopy in the following section.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We also showed that the increase in tissue heating, due to excitation with longer wavelengths, is not as large as water absorption increase for longer wavelengths. This increase in heating may be an acceptable trade-off for leveraging enhanced ND-TPACS and other advantages of ND-2PE [22] in deep tissue imaging applications.…”
Section: Resultsmentioning
confidence: 99%
“…4. The linear dependence of the fluorescence signal generated by ND-TPE on the excitation power of each beam is the characteristic signature of the ND-TPE [22,29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher-order moments and other details of the phase function are also ignored, which will be studied in the future by incorporating other forms of power spectral densities using different local phase smoothing functions [21]. Nonetheless, we expect that this model will be useful to guide further developments of optical microscopy techniques to overcome scattering such as non-degenerate two-photon microscopy [22], and three-photon microscopy [23].…”
mentioning
confidence: 99%